Analisis Faktor Yang Mempengaruhi Keputusan Seseorang Menjadi Sport Photographer - Ananda Rafli Akbar Susanto; Ginanjar Rahmawan (Universitas Kristen Indonesia Toraja, 2023)
This research is to analyze the factors that influence a person's decision to become a sport photographer. The purpose of this research is expected to be useful, both theoretically and practically is expected to provide additional knowledge studies for readers. This research uses qualitative approach by referring to the case study research strategy. The qualitative approach is data obtained such as the results of observations, interviews, photo shoots, document analysis, field notes, no expressed in the form of numbers. The majority of the informants are active people in the world sports photography even though I had never heard of sports photography before. After analyzed, found factors that influence informants in making decisions to be a sports photographer. This study describes several factors in the decision process decision to become a sports photographer. Based on this research, it was found that taking The decision to become a sports photographer is: 1) Opportunity, 2) Simple work flow, 3) Flexibility, 4) Passion.